Precisiones metodológicas acerca de los indicios paleopalino-lógicos de agricultura en la prehistoria de la Península Ibérica - López Sáez, J.A.; López Merino, L. (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
The separation of the pollen of wild Poaceae species from that of domesticated cereal crops if of considerable importance to archaeologist studying Holocene vegetational and agricultural change. This paper assesses the reliability of one available key for identifying sub-fossil grass pollen from the Iberian Peninsula Prehistory.